JURIDICAL ANALYSIS OF THE EVIDENTIARY PRACTICE IN CRIMINAL CONSPIRACY IN NARCOTICS CASES - Hasibuan, Imelda; Japri, Muhammad; Ratnasari, Desy (JILPR Journal Indonesia Law and Policy Review, 2025)
This research aims to analyze the implementation of evidence and criminal liability in the offense of conspiracy to commit narcotics crime, as well as to evaluate the legal considerations of judges in delivering a not guilty verdict to the defendant based on the Supreme Court Decision Number 1488 K/Pid.Sus/2021. The problems in this case highlight the complexity of proving the involvement of actors in a conspiracy, especially in narcotics cases classified as extraordinary crimes. This study also examines the validity of the evidence and the conformity of law enforcement with the principles of justice and legality. The method used in this research is normative juridical, using statutory, conceptual, and case approaches. The data is collected through literature review and judicial decisions, then analyzed qualitatively using the theory of justice, theory of evidence, and theory of criminal responsibility. This approach allows the researcher to examine the application of legal norms and principles in the practice of law enforcement against conspiracy in narcotics crime. The results of the research show that the process of proving conspiracy in narcotics cases does not fully align with the principle of due process of law due to the lack of technical evidence convincing enough for the judges. Criminal liability in this case cannot be imposed collectively without strong individual evidence. Moreover, the Supreme Court's decision to reject the prosecutor’s cassation reflects the limited scope for legal correction in not guilty verdicts. This highlights the need for regulatory reform and strengthening the capacity of law enforcement officers to handle narcotics crimes in a more comprehensive and fair manner.